Seasonal and annual variation in the food habits of Apennine brown bears, central Italy - CIUCCI, Paolo; BOITANI, Luigi; Tosoni, Elisabetta; Di Domenico, Giovanna; Quattrociocchi, Fausto (Journal of Mammalogy, 2014)
Only scanty and outdated knowledge is available on the food habits of the Apennine brown bear (Ursus arctos marsicanus) population, despite its critical conservation status. Based on 2,359 scats, collected from June 2006 through December 2009, we documented seasonal and annual variation in the diet of this bear population within its 1,294 km2 core distribution in Abruzzo, Lazio and Molise National Park and its external buffer area in central Italy. Using correction factors to estimate digestible energy, we revealed substantial consumption of plant matter by bears, including herbaceous vegetation in spring (31.7 ± 25%) and early summer (19.0 ± 7%), a variety of naturally occurring berries in summer (56.5 ± 14%), and hard mast (66.9 ± 21%), largely supplemented by fleshy fruits (26.3 ± 18%), in the fall. Bears also consumed insects, mostly ants, in early summer (38.3 ± 7%), and wild ungulates in spring (10.2 ± 11%). Hard mast production strongly influenced year-to-year variation in the diet. High-quality foods, such as berries and other fleshy fruits, were increasingly consumed by bears in years of low to null hard mast productivity, suggesting that habitat productivity is currently high and diversified enough to allow bears to avoid the risk of nutritional stress during occasional hard mast failures. Nevertheless, as exemplified by a negative trend in late-summer consumption of buckthorn berries (Rhamnus spp.) by bears, our findings demonstrate the need to implement management strategies that will ensure long-term habitat productivity and provide optimal foraging opportunities for Apennine brown bears.